Serum Endoglin and Endocan Levels in Rosacea and Their Association with Cardiovascular Risk Factors: A Case-Control Study - Melodi Çekiç; Ayşın köktürk; Lülüfer Tamer; Rojda Tanrıverdi (Dermatology Practical & Conceptual, 2025)
Introduction: Rosacea, a chronic skin disease characterized by facial redness, is believed to involve inflammation and angiogenesis in its pathogenesis. Endocan and endoglin, biomarkers associated with vascular and inflammatory processes, might play roles in rosacea and cardiovascular comorbidities.